Students' acceptance to self-archive in institutional repositories towards a unified view - Fatin Amirah Masrich; Noraisah Dili; Umi Amneezatun Hamzah; Malisa Muhammed; Nurafida Aidi; Sailendra Kisar (IGI Global, 2016)
This paper aims to examine the students' acceptance on using self-archive in open access repositories guiding by the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This paper utilized convenience sampling method, with a total of 204 sets of self-administered questionnaire collected among the students of public higher learning institution in Federal Territory of Labuan, Malaysia. Multiple regressions were performed to examine the relationships between performance expectancy, effort expectancy, social influence, and facilitating conditions towards the intention to use self-archive in institutional repository. The findings revealed that the students behavioural attention on the acceptance of using self-archive in repository were positively influence by social influence and facilitating condition. The repository administrators shall increase the efforts to enhance the quality of the repository as well as encouraging students' interest to use the service.